An unexpected discovery of a new subgenus and a species of Plusiocampa (Campodeidae, Diplura) alongside an overview of Central European subterranean campodeids - Sendra, Alberto; Weber, Dieter (European Journal of Taxonomy, 2018)
An unexpected new subgenus and species of Campodeidae (Diplura), Plusiocampa (Pentachaetocampa) inopinata subgen. et sp. nov., a troglobitic species found in Schallsinger Höhle in an isolated karstic region in southwestern Germany is described. The new taxon shows two unique characters for the genus Plusiocampa: five dorsal femoral macrosetae and the presence of g1-glandular setae in females. Two other Plusiocampa species have been studied and taxonomic remarks made for them; both are also cave dwelling species from Germany: Plusiocampa dobati Condé in Dobat, 1975 studied from eight caves in the Swabian Alb, and one unnamed species of Plusiocampa (Plusiocampa) from four caves in the Franconian Alb. The biogeographical and taxonomic affinities among Plusiocampa species of Central Europe are discussed. The distribution of Plusiocampa species in Central Europe runs alongside the frontier of the Pleistocene glaciations, with non-troglomorphic Plusiocampa species adjacent to the glacial limits and troglomorphic Plusiocampa species below. Worthy of note is the presence only in the northeast of the Central Alps of two relict Plusiocampinae species, the already known Hystrichocampa pelletieri Condé, 1948 and the new species P. (P.) inopinata subgen. et sp. nov.